ANALISIS KESIAPAN BELAJAR SISWA PADA MATERI REAKSI REDUKSI DAN OKSIDASI KELAS X MAN 2 FILIAL PONTIANAK - Rita Kurnia Sari (Universitas Muhammadiyah Pontianak, 2018)
This study is motivated by the student low readiness and learning mastery in Chemistry class. It is aimed at investigating the student readiness in oxidation-reduction (redox) reaction class. This study used a descriptive case study. As many as 27 students of MAN II Filial Pontianak of Academic Year 2017/2018, selected by purposive sampling technique, participated in this study. The data collection tools were observation, questionnaire, and interview. The average result of this study indicated that student readiness in learning was good (61,97%), especially in physical category by 100% (outstanding), in mental category by 33,33% (fair), in emotional category by 95,06% (outstanding), in necessity category by 62,96 (good ), and in mastery category by 18,52% (poor). Additionally, the result of the questionnaire showed that readiness in learning was 75,86% (very good), particularly in physical category by 81,48% (Excellent), in mental category by 71,60% (very good), in emotional category by 71,24% (very good), in necessity category by 71,29 (very good ), and in mastery category by 77,16% (very good). Therefore, teachers are expected to educate the students about the importance of reading in learning. Also, school is encouraged to enhance the quality of the facilities in learning